Neural network controller for DC motor using MATLAB application - Norazlina, Ab. Rahman (2008)
The purpose of this study is to control the speed of direct current (DC) motor with Artificial Neural Network (ANN) controller using MATLAB application. The Artificial Neural Network Controller will be design and must be tune, so the comparison between simulation result and experimental result can be made. The scopes includes the simulation and modeling of direct current (DC) motor, implementation of Artificial Neural Network Controller into actual DC motor and comparison of MATLAB simulation result with the experimental result. This research was about introducing the new ability of in estimating speed and controlling the permanent magnet direct current (PMDC) motor. In this project, ANN Controller will be used to control the speed of DC motor. The ANN Controller will be programmed to control the speed of DC motor at certain speed level. The data from ANN Controller is sent to the DC motor through an interface circuit or a medium called DAQ card. The sensor will be used to detect the speed of motor. Then, the result from sensor is fed back to ANN Controller to find the comparison between the desired output and measured output.